Career development, compensation, job security, workplace environment and employee loyalty at Syarikat Air Darul Aman (SADA) / Khairul Asraf Ghazali - Ghazali, Khairul Asraf (2019)
The purpose of this study is to identify the most contribute factor to employee loyalty along with the relationship with each of the variables among employees at Syarikat Air Darul Aman (SADA). The evidence in this research are supported by previous article, journal and report from other researchers and expertise. In this research, Simple Random Sampling being used for sampling technique. Meanwhile, sample size for the organization are being presented with the calculation based on Krejcie and Morgan table. For statistic calculation, researcher use SPSS version 22.0. Researcher use mean and standard deviation to find the most contribute factor to employee loyalty and it also strengthen with Pearson Correlation relationship between Independent and Dependent variables. As for the result, all the findings prove that each Independent variable has a strong relationship with employee loyalty. However, career development has been classified as the most influenced factor to employee loyalty at Syarikat Air Darul Aman (SADA). To conclude, this study also helps the organization to improve their relationship among the employees. I hope that my recommendation is being considered whether for the organization or any future research